Philosophy of education: the formation of planetary-cosmic personality type - Базалук, О.А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
Considered strategic goal of philosophy of education - the formation of planetary-cosmic personality type. Based methodology of forming the image of man of the future.